(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2020)
The reasons for an early Cenozoic age of the basal part of the Borghetto succession, as an alternative to an upper Cretaceous age, are re—proposed. Moglio Pelites have been found at the stratigraphic base of the "prepiemontese" succession of Borghetto. This proves that the paleogeographical location of the above succession had to be contiguous with the one of the Moglio—Testico unit, which was therefore interposed between the Borghetto deposition area and the San Remo one. The olistostromes of Moglio Pelites retraceable inside and at the top of the mentioned Borghetto succession show that in the domains, which the western Liguria flysch come from, the tectogenesis started before the San Remo—M. Saccarello unit had been overthrust towards the external Brianzonese.